Casualty behaviours during incidents involving hazardous materials. (August 2022) - Long, F.; Carter, H.; Majumdar, A.
Abstract: Purpose: Human Behaviour during emergency situations is a crucial component of any response. The ability of responders to effectively engage with casualties is critical to ensuring that any instructions given are followed and in doing assist rather than hinder the response. In order to improve the likelihood of this occurring it is essential to understand what drives decision making during emergencies in order to be able to effectively influence these. This paper will seek to establish what these behaviours are likely to be and what is likely to influence these in order to inform responder tactics and training. Design/methodology/approach: This paper seeks to develop a psychological model of casualty behaviour during a hazardous materials evacuation. The study utilises a survey of members of the public evacuated from their homes or places of work due to a fire impacting an ammonia tank in February 2019 at the Ocado distribution warehouse in Andover. The results of this survey were used to validate a hypothesised psychological model utilising Path Analysis. Findings: The research identifies the importance of recognising the ability of casualties involved in emergency situations to remain rational and utilise information and instructions given to them. The paper highlights the importance which trust plays in engaging with casualties in order to provide effective information and instructions and how trust is constructed of both legitimacy and competency and influenced by the communications of responders. Most crucially the paper identified how trust during an emergency situation is the key driver of whether casualties are likely to co-operate with instructions and emergency responders. Originality/value: The research utilised real world data to validate findings demonstrating the need for emergency responders to effectively engage with casualties and has implications for both guidance and training of emergency responders in managing casualties.